Throttling effect on the performance and emissions of a multi-cylinder gasoline fuelled spark ignition engine - Hamada, Khalaf I.; Rahim, M. F.; Raham, M. M.; A. Bakar, Rosli (Universiti Malaysia Pahang, 2022)
The throttle mechanism, a regulatory technique of engine output, is accompanied by a loss of some energy. The effect of intake air throttling on the performance and emissions of a multi-cylinder spark ignition gasoline engine was experimentally investigated. The engine was coupled to a hydraulic dynamometer equipped with a customized cooling system for both the engine and dynamometer. Experimental tests were performed for various engine speeds and air-fuel ratios at the WOT and POT conditions with optimized ignition timing. The acquired results recorded that a better engine operation could be achieved with WOT in terms of bmep, bsfc, ηb, CO, CO2 and UHC compared to POT. At the same time, the worst trend at WOT was noticed for the NOx concentration due to the higher conversion efficiency of fuel combustion. In terms of engine speed for both WOT and POT conditions, operating at 3000 rpm represents the minima of ϕ, bsfc, CO and UHC; and the maxima of ηb, CO2 and NOx with some fluctuation on both sides of this point. Maximum recorded values of ηb were about 30.55% and 28. 55%, while the minimum values of bsfc were about 274 and 293 g/kW.h for the WOT and POT conditions, respectively. The maximum bmep was obtained at 2500 rpm at WOT and POT conditions with values of about 940 kPa and 904 kPa, respectively. Maximum recorded values of NOx were about 1525 and 977 ppm for the WOT and POT conditions, respectively.